2021
DOI: 10.3389/fpsyg.2021.701689
|View full text |Cite
|
Sign up to set email alerts
|

Too Good to be Liked? When and How Prosocial Others are Disliked

Abstract: Outstandingly prosocial individuals may not always be valued and admired, but sometimes depreciated and rejected. While prior research has mainly focused on devaluation of highly competent or successful individuals, comparable research in the domain of prosociality is scarce. The present research suggests two mechanisms why devaluation of extreme prosocial individuals may occur: they may (a) constitute very high comparison standards for observers, and may (b) be perceived as communal narcissists. Two experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 81 publications
(151 reference statements)
0
3
1
Order By: Relevance
“…With regard to the longitudinal associations between peer acceptance and prosocial behavior, the cross-lagged panel analysis showed that prosocial behavior positively predicted peer acceptance over time, but peer acceptance did not predict future prosocial behavior. Contrary to some findings suggesting that, in some cases, prosocial behavior can elicit dislike from others (e.g., Boileau et al, 2021 ), the results of this study show that engaging in friendly, kind behaviors such as sharing, helping, or comforting others, helps adolescents gain more acceptance from their peers. However, no evidence was found that being well-liked led to increases in prosocial behavior.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…With regard to the longitudinal associations between peer acceptance and prosocial behavior, the cross-lagged panel analysis showed that prosocial behavior positively predicted peer acceptance over time, but peer acceptance did not predict future prosocial behavior. Contrary to some findings suggesting that, in some cases, prosocial behavior can elicit dislike from others (e.g., Boileau et al, 2021 ), the results of this study show that engaging in friendly, kind behaviors such as sharing, helping, or comforting others, helps adolescents gain more acceptance from their peers. However, no evidence was found that being well-liked led to increases in prosocial behavior.…”
Section: Discussioncontrasting
confidence: 99%
“…Indeed, recent findings have shown that prosocial behavior could even decrease peer acceptance. In an experiment with university students, being outstandingly prosocial was found to decrease acceptance (e.g., likeability) and provoke rejection (Boileau et al, 2021 ). Likewise, using four different data sets, it has been demonstrated that individuals who were particularly generous in a public goods game became excluded by the group (Parks & Stone, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Helping others could be used to self-enhance (Italiano, 2017;Konrath et al, 2016;Nacheva, 2019), and narcissism levels increase after helping others (Giacomin & Jordan, 2014). In addition, extremely prosocial people are perceived as communal narcissists (Boileau et al, 2021).…”
Section: The Narcissistic Sanctity and Heroism Conceptmentioning
confidence: 99%